Factors associated with women’s choice for mode of cervical sampling in future cervical cancer screening - Natalija Berza; Jana Zodzika; Anda Kivite-Urtane; Alise Curkste; Ilva Pole; Mari Nygard; Kersti Parna; Anneli Uusküla (PLoS ONE, 2026)
Background Cervical cancer (CC), primarily caused by persistent high-risk human papillomavirus (HR-HPV) infection, remains a major public health challenge, with Latvia experiencing substantially higher incidence and mortality rates than the European average. HR-HPV self-sampling is an effective and acceptable screening method, yet some women continue to prefer clinician-collected sampling. Evidence on factors associated with reluctance to adopt self-sampling in the Baltic region is limited. This study examined demographic, socioeconomic, behavioral, and health-related characteristics linked to women’s preferences for future cervical cancer screening modalities. Materials and methods This cross-sectional study was conducted in Latvia between February 2021 and April 2022. Women attending general practitioners or the Colposcopy Unit of Riga East University Hospital were invited to perform unsupervised HR-HPV self-sampling using written and visual instructions, followed by a structured questionnaire. Collected data included demographic and socioeconomic characteristics, health status, health behaviours, emotional responses to self-sampling, and preferred sampling modality for the next screening round. Descriptive statistics and Chi-square tests were used to assess differences in emotional responses and preferences. Factors associated with preferred sampling modality were identified through univariate and multivariate multinomial logistic regression. Statistical significance was set at p < 0.05. Results A total of 1,217 women were included. Overall, 45.9% preferred clinician-collected cervical sampling, 42.6% preferred self-sampling, and 11.5% expressed no clear preference. Women who preferred self-sampling reported significantly lower embarrassment and discomfort during the procedure (p < 0.001). Most participants expressed positive emotional responses. The main reason for preferring clinician-collected sampling (81.0%) was a lack of confidence in performing self-sampling correctly. Multivariate analysis showed a higher preference for clinician-collection among women recruited from colposcopy settings and those with more recent gynecological visits, whereas former or occasional smokers were less likely to prefer clinician collection. Higher BMI (≥25) and non-Latvian nationality were associated with indecision regarding future sampling preference. Conclusion HR-HPV self-sampling was generally well accepted and may help engage women less likely to attend traditional screening. Preference for clinician-collection was shaped mainly by medical history and nationality. Emotional factors may also influence screening choices and should be considered in future implementation strategies.